Panama : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that Panama's economic performance remains buoyant. Real GDP growth averaged about 8.5 percent over the past decade, the highest in Latin America, supported by an ambitious public investment program, and accompanied by strong reduction in unemployment, poverty, and income inequality. After exceeding 10 percent in 2011-2012, growth slowed to 8.4 percent in 2013 reflecting mainly a decline in Colon Free Zone activity and in Canal traffic. Growth is expected to remain strong over the medium term. Inflation is moderating, owing to the deceleration of international food and oil prices. The baseline outlook is favorable, with moderate risks.